Legal Regulation of Surrogate Maternity - V. A. Tsvetkov (Сибирское юридическое обозрение, 2012)
The article is devoted to the analysis of legal problems connected with the introduction of the Surrogate Maternity Institution. The author offers some ways of their settlement.